Rancang Bangun Aplikasi Absensi Guru dan Staff di MA Taruna Teknik Aljabbar Berbasis Android dengan Metode Qr Code Menggunakan Kodular - Riski Pardomuan Siregar; Faizin Ridho (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
Attendance system reports are very important in various institutions, whether companies, factories, hospitals or educational institutions, where attendance reports are an important assessment of a person's work results or discipline. The school attendance system is no exception, where we can assess the attendance of teachers and staff which is very much needed and has even become one of the main priorities for giving grades to teachers and staff. Based on the results of an interview with the Head of the Al Jabbar Technical Cadets on 23 August 2022. Mr. Indra Sakti Siagian, S.Pd as Kamad explained that the existing system is in the form of manual attendance, namely using books, a system that still has weaknesses that are vulnerable to being torn, lost and damaged and it really takes a long time to recap attendance data so that attendance reports are not produced on time, This system development method starts from the analysis, design, coding, testing and support stages. Meanwhile, several methods in the data collection process were observation and interviews. The result of this research is an attendance application that utilizes Qr Code and was developed with the Kodular platform. And it can be concluded that the Teacher/Staff attendance system using Qr Code at the Al Jabbar Engineering Taruna MA really helps the Principal in monitoring Teacher/Staff attendance and facilitates the teaching and learning process and improves the quality of the SDM at the Al-Jabbar Taruna MA.